Sinergi Implementasi Program Pusat Informasi Konseling Remaja (PIK-R)-Hipnotherapy dalam Menangani Triad KRR (HIV-AIDS, Napza, Seksualitas) di Kecamatan Gayam, Kabupaten Bojonegoro - Agus Ari Afandie; Rahmawati Rahmawati; Siti Patonah (IKIP PGRI Bojonegoro, 2019)
Gayam and Brabowan villages are areas in Gayam sub-district, which are in ring 1 of Exxon Mobil oil and gas exploration. Changes from the agrarian region to the oil industry are shifting in the economic, cultural, and social sectors of society, which are vulnerable to negative influences such as alcoholic drinking, drugs so that adolescents are at risk of being affected by TRIAD KRR (sexuality, HIV-AIDS, drugs). The purpose of this program is teenagers understand and practice healthy lifestyles, morality, resilience, and prepare themselves to become the Indonesian Planning Generation through the synergy of the PIK-R program and hypnotherapy. This program synergizes youth information and counseling programs with hypnotherapy in the PIK-R container,Â and giving health services, facilitating referral and fostering religious, and moral as well as requiring cross-program and cross-sector collaboration. The results showed that the knowledge and life skills of adolescents, increase in TRIAD KRR (sexuality, HIV AIDS and drugs) by 24.2%. Peer counselor ability has increased by 60%. Youth motivation in developing and managing PIK-R increased by 33.3%. Health checks carried out through HIV AIDS screening in adolescents and 100% free ofÂ HIV AIDS. Adolescents are able to detect the symptoms and signs of HIV AIDS that are beneficial to theÂ community. Provision of religious knowledge must be carried out consistently in order to form a noble character to prevent the impact of transcultural culture. Collaboration are created to establish a moral engagement so that the program runs sustainably and a generation of planning is created (GENRE).